Advanced practice physiotherapists are effective in the management of musculoskeletal disorders: a systematic review of systematic reviews. (December 2021) - Vedanayagam, Mario; Buzak, Martina; Reid, Duncan; Saywell, Nicola
Abstract: Background: There are increasing demands for orthopaedic specialist services due to the increasing burden of musculoskeletal (MSK) disorders. This situation creates a barrier for patients to access appropriate health care. Advanced practitioner physiotherapists (APP) may provide an alternative service for patients with MSK disorders. Objective: To evaluate the evidence on whether APPs are accurate at diagnosis, can triage appropriately and improve patient treatment outcomes and access to care for patients with musculoskeletal disorders. Data sources: CINAHL, MEDline, Web of Science, SPORTdiscus, SCOPUS and AMED between January 2000 and March 2020. Study selection: Systematic reviews evaluating the efficacy of APPs, in any healthcare setting, treating patients of any age range with MSK disorders, in comparison to orthopaedic surgeons or doctors. Data extraction and synthesis: Two researchers independently extracted and synthesised data according to the inclusion and exclusion criteria. Methodological quality was independently assessed by two reviewers using the AMSTAR tool. A third reviewer resolved discrepancies. Results: Thirteen systematic reviews met the inclusion criteria. The evidence consistently found APPs are accurate at diagnosis, can triage appropriately, and improve patient treatment outcomes and access to care. There was a lack of high-quality primary studies in the included reviews, however, the highest quality studies had similar findings. Limitations: A meta-analysis was not possible due to heterogeneity of outcome measures. There was an overlap of primary studies which may cause bias. Conclusion: The evidence of varying quality consistently shows that APPs can accurately diagnose, appropriately triage and effectively manage patients with musculoskeletal disorders in various clinical settings.